Correlation of preoperative co-morbidities with post-operative outcomes in patients operated for hip fractures - R Goyal, Rakesh; Makwana, Harsha; M Bhavsar, Neel; A Musa, Rameez; R Patel, Pankaj (International Journal of Medical Research and Review, 2016)
Introduction: As the population ages, disability and death is becoming more common in which hip fracture is one of the commonest cause. The purpose of this study is to analyse the effect of preoperative co-morbidities on postoperative outcomes in patients operated for hip surgery. This would also provide a reference for improved treatment and perioperative planning in order to have better survival chances in postoperative periods. Methods: This is an observational study in elderly patients ranging from 50-110 years of age for isolated hip fractures operated at a tertiary care hospital in Ahmedabad from January 2015 to January 2016. Patients were analyzed for one month mortality after hip fracture fixation. The co-morbidities encountered were then co-related with mortalities and conclusion drawn. Results: A total of 376 patients (54 percent males, 46 percent females) were taken for study. Analysis for one month mortality after hip fracture fixation showed that 7.7 percent deaths (45 percent males, 55 percent females) occurred within one month of operation. 51.7 percent of patients expired in first week. 17.2 percent in second week and 31.1 percent in later half of month. Conclusion: Study showed that postoperative mortality was directly proportional to the number of pre-operative co-morbidities. Patients who had ≥ 3 comorbidities had higher mortality risk, with two co-morbidities moderate risk and those having one or no comorbidity had higher survival chances in postoperative period. The presence of 3 or more comorbidities is the strongest preoperative risk factor for postoperative outcome.